Konstruksi Sosial Sabung Ayam (Tajen) (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
This qualitative study describes the social construction of cockfighting (tajen) in Binyan Village. Tajen rah and Tajen cocongan remain essential for the ceremony. Tajen tabuh rah and Tajen cocongan are cultural constructs based on ancestral traditions. The rules of tajen tabuh rah and tajen cocongan are regulated based on current conditions to make the community more bearable while still providing entertainment. Only a few performers in the arena used simple gambling methods to gamble. Social construction begins when communities externalize adatbased tajen rules by extending the performing of tajen times and adding gambling elements. Furthermore, gambling is internalized by repeating the simple rules of tajen and involving several actors in both sets. Tajen tabuh rah and Tajen cocongan became objectified as a series with a gambling element in the smaller arena